2019
DOI: 10.1101/721985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NAD+repletion rescues female fertility during reproductive ageing

Abstract: 2Female infertility is a common and devastating condition with life-long health, emotional and 3 social consequences. There is currently no pharmacological therapy for preserving oocyte 4 quality during aging, which is the strongest risk factor for infertility. This leads to an age 5 dependent decline in natural conception and IVF success rates (1). Here, we show that this is 6 due in part to declining levels of the metabolic cofactor nicotinamide adenine dinucleotide 7 (NAD + ), and that restoring NAD + level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Interestingly, a recent work reported a similar finding, showing that supplementation of NMN in drinking water for 4 weeks prominently rejuvenated oocyte quality and restored the fertility of aged mice (Bertoldo et al, 2020). They further indicated that Sirt2 overexpression recapitulated the benefits of NMN treatment (Bertoldo et al, 2020). Our data validated that Sirt1 was also implicated in the effects of NMN on aged oocytes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, a recent work reported a similar finding, showing that supplementation of NMN in drinking water for 4 weeks prominently rejuvenated oocyte quality and restored the fertility of aged mice (Bertoldo et al, 2020). They further indicated that Sirt2 overexpression recapitulated the benefits of NMN treatment (Bertoldo et al, 2020). Our data validated that Sirt1 was also implicated in the effects of NMN on aged oocytes.…”
Section: Discussionsupporting
confidence: 88%
“…In particular, NMN restores mitochondrial function of aged oocytes to suppress accumulation of ROS and DNA damage, reducing apoptosis. Interestingly, a recent work reported a similar finding, showing that supplementation of NMN in drinking water for 4 weeks prominently rejuvenated oocyte quality and restored the fertility of aged mice (Bertoldo et al, 2020). They further indicated that Sirt2 overexpression recapitulated the benefits of NMN treatment (Bertoldo et al, 2020).…”
Section: Discussionmentioning
confidence: 58%
“…Oocyte quality and quantity is the rate limiting factor in the production of embryos in vitro [5]. Unlike most cells that undergo constant regeneration from precursor stem cells, the number of oocytes contained within the ovaries is finitely set during prenatal development [6,7] and determines the reproductive lifespan of the female.…”
Section: Introductionmentioning
confidence: 99%
“…In humans and mice, NAD + deficiency brought about by aberrant expression of de novo synthesis pathway enzymes leads to birth defects [16]. In addition, supplementation of NAD + precursors, including nicotinamide mononucleotide and nicotinic acid, both in vitro and in vivo improved mouse oocyte quality and embryo development [5,17,18]. Furthermore, Sirtuins (SIRTs) and poly-ADP-ribose polymerases (PARPs) consume NAD + , and are known to play essential roles during oocyte maturation [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…BAT transplantation could also improve oocyte quality of aging mice (28). However, the upper and most of other anti-oxidants, and BAT transplantation could not increase PFR, and non-enzymatic anti-oxidants are less efficient than enzymatic ROS detoxifiers such as SOD (superoxide dismutase) and Gpx (glutathione peroxidase) (23,25,26). It has been reported that supplement of melatonin (29), quercetin (30), or resveratrol (31) could improve both PFR and oocyte quality by reducing ROS and apoptosis.…”
Section: Introductionmentioning
confidence: 99%